217k views
5 votes
Which equation is equivalent to 3 (2x + 10) -10x = 26 ?

a 16x + 30 = 26
b -4 + 30 =26
c 6x + 10 =26
d -4x +10 = 26

User Duroth
by
6.0k points

1 Answer

4 votes

Answer:

The answer to this problem is B. Although you have a typo error with "-4" I believe it is "-4x",

Explanation:

The equation is set with distributive property. Simplify that first and then move on to adding like terms.

3(2x + 10) - 10x = 26.

6x + 30 - 10x = 26.

-4x + 30 = 26.

The only equation that looks equivalent is -4x + 30 = 26 in B.

For A, it would of been correct if -10x was 10x, but it is not so mark it out.

For C, it would of been correct if there was no -10x and if there was a -20, but this is not true so mark it out as well.

For D, it would of been correct if there was a -20, but since there is no -20, this is wrong like A and C.

So B is the best option.

User Blagae
by
5.7k points